Estimate the Attenuation and Simulation of dispersion Gaussian pulses propagation in a Single Mode Optical Fiber - Mubarak Hamad Oglah (Tikrit Journal of Pure Science)
we studied Attenuation in Fiber Optics, we used two type of Fibers (Plastic and glass) with length (0.5,5,20m) and (1,20,100m) respectively and used two wavelength laser (660nm, 850nm), we found attenuation increase with 850nm wavelength and 660nm wavelength are the best for the plastic fiber optics, in addition the attenuation which occur from axial gap, axes rotation, inclination angle, transversal displacement are investigated. Influence three values of linear dispersion on Pulse propagation along fiber at seam distance is investigated by simulation using Fourier Method using MATLAB.